Kontribusi Kepemimpinan Pelayan, Manajemen Kesiswaan, Layanan Bimbingan dan Konseling, dan Konsep Diri Terhadap Budaya Sekolah Pada Siswa - N. Reksa; A.A.G. Agung; I.P.W. Ariawan (Jurnal Administrasi Pendidikan Indonesia, 2021)
This study aims to determine the amount of contribution between the variables of servant leadership, student management, guidance and counseling services and self-concept to school culture. This research is classified as ex-post facto with multiple linear regression analysis design. The population in this study was 1,253 people. The research sample was taken randomly, amounting to 100 students. Data were collected by using a questionnaire with likert scale from the variable servant leadership, student management, guidance and counseling services and self-concept and school culture. Besides, the method of documentation and observation were used as complementary methods in obtaining the number of students in the school. The results showed that (1) there was a contribution of principal servant leadership to school culture by 0.561% 2) there was a contribution of student management to school culture by 3.36%; 3) there is a contribution of guidance and counseling services to school culture by 22.44%; 4) there is a contribution of self-concept to school culture by 24.68%; 5) there is a simultaneous contribution between servant leadership, student management, guidance and counseling services, and self-concept to school culture by 51.041%. This study has implications for the role of the principal in leading the school and the condition of the learning atmosphere.